Actual problems of studying regional media - Ashirbekova, Г.Ш.; Yesnazarova, Р.М.; Bakhtiyarkyzy, С.Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The article analyzes the current problems of studying regional media. The author, comparing the methods of studying the history of the press and the data contained in the works of scientists, puts forward the need to systematize the history of regional newspapers in the future. Comparing research papers, shows the discrepancy of data in the history of the regional press using a table. It also emphasizes the place and important activity of regional media in domestic journalism and defines the importance of mastering technological capabilities in the digital age. The author relied on a number of research papers related to regional media and demonstrated their innovation. Having analyzed the current problems of studying regional media, I focused on their significance. Also defines the issues that need to be considered in the future. The article clearly outlines the disadvantages of using the new media capabilities of regional media. It is established that foreign regional media researchers need to pay attention to research methods and consider problematic issues in the activities of regional media.